Proceedings of the 15th Conference of the European Chapter of The Association for Computational Linguistics: Volume 1 2017
DOI: 10.18653/v1/e17-1025
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Pragmatic Phenomena on Irony Detection in Tweets: A Multilingual Corpus Study

Abstract: This paper provides a linguistic and pragmatic analysis of the phenomenon of irony in order to represent how Twitter's users exploit irony devices within their communication strategies for generating textual contents. We aim to measure the impact of a wide-range of pragmatic phenomena in the interpretation of irony, and to investigate how these phenomena interact with contexts local to the tweet. Informed by linguistic theories, we propose for the first time a multi-layered annotation schema for irony and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 27 publications
4
36
0
Order By: Relevance
“…Our monolingual results are comparable to state of the art for the three languages. The CNN architecture trained on cross-lingual word representation shows that irony has a certain similarity between the languages we targeted despite the cultural differences which confirm that irony is a universal phenomena, as already shown in previous linguistic studies [35,24,9]. The manual analysis of the common misclassified tweets across the languages in the multilingual setup, shows that classification errors are due to three main factors.…”
Section: Discussionsupporting
confidence: 83%
“…Our monolingual results are comparable to state of the art for the three languages. The CNN architecture trained on cross-lingual word representation shows that irony has a certain similarity between the languages we targeted despite the cultural differences which confirm that irony is a universal phenomena, as already shown in previous linguistic studies [35,24,9]. The manual analysis of the common misclassified tweets across the languages in the multilingual setup, shows that classification errors are due to three main factors.…”
Section: Discussionsupporting
confidence: 83%
“…ironic vs. not-ironic) or flag irony as part of sentiment annotations. By contrast, Karoui et al (2017) defined explicit and implicit irony activations based on incongruity in ironic tweets and defined eight fine-grained categories of pragmatic devices that realise such an incongruity, including analogy, hyperbole, rhetorical question, oxymoron, etc. While the typology provides valuable insights into the linguistic realisation of irony, the inter-annotator agreement study demonstrated the complexity of identifying such pragmatic devices, hence it is not clear to which extent such the distinction would be computationally feasible.…”
Section: Data Collection and Annotationmentioning
confidence: 99%
“…We exploited data from a set of corpora collected exploiting different approaches: self-tagging or manual annotation or crowd-sourcing 3 . We exploited the corpora developed by (Reyes et al, 2013), (Barbieri et al, 2014), (Mohammad et al, 2015), (Ptáček et al, 2014), (Riloff et al, 2013), (Ghosh et al, 2015), (Karoui et al, 2017), and (Sulis et al, 2016). Besides, we also take advantage of an in-house collection of tweets containing the hashtags #irony and #sarcasm 4 .…”
Section: Task A: Ironic Vs Non-ironicmentioning
confidence: 99%